Induction of Hepatocyte Stimulating Activity by T(3) and Appearance of the Activity despite Inhibition of DNA Synthesis by Adriamycin - Francavilla, A. (1984)
A hepatocyte stimulating activity (HSA) has been extracted from rats that had received an injection of a pharmacological dose of T(3) 20 hours earlier. The injection of HSA from T(3)-treated rats into different recipient rats that had previously had 40% of their liver removed resulted in a significant increase in hepatic DNA synthesis. The injection of saline or HSA from normal rat liver had little or no effect on hepatic DNA synthesis in recipient rats. HSA from the T(3)-treated rats also stimulated DNA synthesis in Novikoff hepatoma cells and primary hepatocytes in culture, and in isolated normal rat liver nuclei in a nuclear incorporating system. In further experiments in which the increased DNA synthesis that follows partial hepatectomy was blocked by adriamycin, HSA appeared in these non-regenerating livers. This latter observation had indicated that the development of HSA is not merely an accompaniment of DNA synthesis.